A Comprehensive Investigation on Potential Risk Factors for NSCL/P in a Rural District of Hebei Province, China. (February 2023) - Chai, Congna; Cheng, Lei; Jiao, Jianjun; Dang, Juan; Jin, Shubin
Background : Non syndromic cleft lip with or without palate (NSCL/P), one of the most common birth defects, is closely related to various risk factors. However, information regarding risk factors for NSCL/P in rural districts in China is very limited thus far. The objective of this study was designed to identify the potential risk factors for NSCL/P in rural districts. Methods : A comprehensive retrospective investigation including 435 NSCL/P patients and 402 healthy children was carried out in Hebei Province, China. Multiple logistic regression analysis and transmission disequilibrium test (TDT) were respectively used to identify non-genetic and genetic risk factors for NSCL/P, and then PLINK was used to explore the relationship between non-genetic and genetic risk factors. Results : The results showed that maternal periconceptional exposure to pesticides and herbicides, as well as low parental education level were involved in the increased risk of NSCL/P, whereas maternal folic acid and multivitamin supplementation use during preconception period were associated with the reduced risk of NSCL/P. TDT analysis identified 2 single nucleotide polymorphisms (SNPs) (rs7078160 and rs4752028) in VAX1 and one SNP (rs17563) in BMP4 as the genetic risk factors for NSCL/P. Further analysis showed that the genetic risk factors were closely related with the negative non-genetic risk factors. Conclusion : Our study identified the potential risk factors for NSCL/P in rural districts, thus providing a theoretical basis for the prevention of NSCL/P occurrence.